Seven ways to prevent biomism - Silveira, Fernando A. O. (Ambio, 2025)
Biomism, the pervasive prejudice, discrimination or antagonism against a given biome, highlights critical and overlooked dimensions of human behavior biases that have consequences for real-world conservation. Here, I propose seven ways to end biomism in educational, scientific and conservation arenas, including (1) the recognition and value of all biomes, (2) use of inclusive language that acknowledges diverse perspectives, (3) preventing research prioritization based on colonial legacies, (4) tailoring biome-specific conservation, management and restoration, (5) adapting legislation to embrace all biomes, (6) developing inclusive regulatory measures and (7) equalizing funding opportunities. Recognizing and addressing biases against specific biomes is essential for fostering a more inclusive and equitable approach to conservation arenas and abandoning long-standing prejudices rooted in colonial legacies, aesthetic preferences and utilitarian views of nature.